The lived experience of Joint Hypermobility and Ehlers-Danlos Syndromes: a systematic review and thematic synthesis. (4th March 2019) - Bennett, Sarah E.; Walsh, Nicola; Moss, Tim; Palmer, Shea
Abstract: Background: Joint Hypermobility Syndrome (JHS) and Ehlers-Danlos Syndrome (EDS) are heritable connective tissue disorders characterised by joint instability, pain, anxiety, depression and poor quality of life. However, peoples' lived experiences are not well understood. Objective: To understand the lived experiences of people with JHS and EDS. Methods: A systematic review was conducted using PRISMA guidelines. Critical appraisal and a thematic synthesis of participants' lived experiences were conducted. Eight online databases were searched from 1990 to February 2018: AMED, CINAHL, EMBASE, MEDLINE, PubMed, PsychINFO, SPORTDiscus and the Cochrane Library. Eligibility criteria were: (1) People with either JHS or EDS, clearly distinguished from generalised joint laxity; (2) Qualitative studies, or mixed qualitative and quantitative studies with qualitative data reported independently and (3) Published in English. Results : A total of nine studies were included. Five main themes were identified: (1) Lack of professional understanding; (2) Restricted life; (3) Social stigma; (4) Trying to 'keep up' and (5) Gaining control. The implications of these results are explored. Conclusions: Further qualitative research is required to examine the impact of JHS/EDS on a wider range of participants and in greater depth.